PENGARUH KECERDASAN SPIRITUAL DN MOTIVASI BELAJAR TERHADAP KEDISIPLINAN SISWA DI MADRASAH ALIYAH PONDOK PESANTREN SYAFA’ATURRASUL TELUK KUANTAN - Fitri, Dina; Zaitun, Zaitun; Yeli, Salmaini (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2025)
This study aims to examine the effect of spiritual intelligence on learning motivation and its impact on student discipline at MAS PP Syafa’aturrasul. This research uses a quantitative approach with a correlational design. The population consists of all students at MAS PP Syafa’aturrasul Teluk Kuantan, totaling 232 students. The sample for this study includes 128 students from grades X and XI. Data collection techniques use questionnaires and documentation. Data analysis techniques involve simple linear regression and multiple linear regression. The results of this study are: First, the level of student discipline at MAS PP Syafa’aturrasul is categorized as moderate at 36.7% and high at 63.3%. , there is a significant influence of spiritual intelligence on student discipline at MAS PP Syafa’aturrasul with an R-square value of 0.123. Second, there is a significant influence of learning motivation on student discipline at MAS PP Syafa’aturrasul Teluk Kuantan with an R-square value of 0.204. Third, here is a significant influence of spiritual intelligence and learning motivation simultaneously on student discipline at MAS PP Syafa’aturrasul Teluk Kuantan with an R-square value of 0.209. Keywords: Spiritual Intelligence, Learning Motivation, Discipline